2019
DOI: 10.1109/access.2019.2945475
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Placement of Inertia and Primary Control: A Matrix Perturbation Theory Approach

Abstract: The increasing penetration of inertialess new renewable energy sources reduces the overall mechanical inertia available in power grids and accordingly raises a number of issues of grid stability over short to medium time scales. It has been suggested that this reduction of overall inertia can be compensated to some extent by the deployment of substitution inertia -synthetic inertia, flywheels or synchronous condensers. Of particular importance is to optimize the placement of the limited available substitution … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…Ref. [21] found that the change of ω α with χ is to leading order proportional to i u 2 αi δγ i , where u α is the eigenvector of the Laplacian corresponding to λ α and δγ i = (d i /m i − γ). For the lowest modes which are approximately constant over large areas, u 2 αi can be factored out and i∈area δγ i ≈ 0, assuming that the distribution of δγ i is independent of the geographical location.…”
Section: B Eigenvectors and Eigenvaluesmentioning
confidence: 99%
See 2 more Smart Citations
“…Ref. [21] found that the change of ω α with χ is to leading order proportional to i u 2 αi δγ i , where u α is the eigenvector of the Laplacian corresponding to λ α and δγ i = (d i /m i − γ). For the lowest modes which are approximately constant over large areas, u 2 αi can be factored out and i∈area δγ i ≈ 0, assuming that the distribution of δγ i is independent of the geographical location.…”
Section: B Eigenvectors and Eigenvaluesmentioning
confidence: 99%
“…The optimal placement of inertia and damping has further been investigated using perturbation theory in Ref. [21]. In a more general context, Ref.…”
Section: Matrix Perturbation Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The more severe is the shock, the larger is the fraction of people that could be displaced in a region, thereby changing the global landscape of migration patterns. Adapting techniques from the study of vulnerability and leadership in network dynamical systems (Fitch & Leonard, 2015;Porfiri & Frasca, 2018;Pagnier & Jacquod, 2019), we propose a sensitivity analysis to examine the specific effect of a local shock on global migration patterns. In this context, we apply a perturbation at a given node (that is, an increase in the number of individuals who are willing and able to migrate) and study its cascading effects in any other node.…”
Section: Accepted Articlementioning
confidence: 99%
“…Γ has two eigenvalues which can be defined as 1 = 2 = 1. According to eigenvalue perturbation theory [22], two following matrices are constructed.…”
Section: Proof Of Convergencementioning
confidence: 99%